Scoping review of nursing-related dissemination and implementation research in German-speaking countries: Mapping the field / Scoping Review zum Stand der pflegebezogenen Disseminations- und Implementierungsforschung in deutschsprachigen Ländern: eine Bestandsaufnahme - Hoben Matthias; Berendonk Charlotte; Buscher Ines; Quasdorf Tina; Riesner Christine; Wilborn Doris; Behrens Johann (Sciendo, 2014)
Implementing evidence-based innovations into care practice is a complex, slow and haphazard process. Dissemination and implementation (DI) research seeks to understand and optimize that process, to close gaps between research and practice and to improve quality of care. While there is a growing body of international DI research, little is known about the number and types of DI research studies and the DI topics studied in German-speaking nursing settings. This scoping review therefore evaluates the state of nursing-related DI research in German-speaking countries, discusses these results in light of the international state of DI research and provides directions for future research. We searched international databases (Web of Knowledge including Medline, CINAHL, PsycInfo, and GeroLit), German library meta-search engines, six German-language key trade journals, and reference lists of included articles. In total, 186 references representing 140 research projects were included in our review. Quality appraisal used five validated checklists. Methodological quality of the included studies was generally low. A total of 92 studies assessed the effects of DI strategies, 67 studied DI barriers and facilitators, 64 evaluated the impact or characteristics of DI processes, and 5 reported on the development or validation of DI research tools. None of the included studies focussed on methodological questions of DI research or on development and testing of DI theories and models. Future nursing-related DI research in German-speaking countries should particularly focus on these latter topics. Taking into account the international state of DI research will be especially crucial for those research activities.